Non-High-Density Lipoprotein-to-High-Density Lipoprotein Cholesterol Ratio as a Predictive Biomarker for Diabetic Retinopathy Risk: A Population-Based Analysis of US Adults - Zhang, Zhirui; Liu, Changxing; Zhao, Lingying; Tan, Xufang; Yu, Ximing; Wang, Jiadi; Yao, Jing (Ophthalmic research, 2025)
Introduction: Diabetic retinopathy (DR) is a severe complication of diabetes, and lipid imbalances play a key role in its progression. The non-high-density lipoprotein cholesterol-to-high-density lipoprotein cholesterol ratio (NHHR) has been identified as a predictor of cardiovascular diseases, but its link to DR remains unclear. This study aimed to assess the association between NHHR and DR risk in diabetic patients. Methods: Data from the 2005–2018 National Health and Nutrition Examination Survey (NHANES) were analyzed. Multivariate logistic regression models were used to evaluate the relationship between NHHR and DR. Nonlinear associations were assessed using restricted cubic spline analysis. Results: Of the 4,935 participants, 1,193 had DR. Higher NHHR was strongly associated with increased DR risk. Each unit rise in NHHR increased the risk by 19% (OR = 1.19, 95% CI: 1.07–1.31, p < 0.05). In quartile analysis, participants in the highest NHHR quartile had nearly double the risk of DR compared to those in the lowest quartile (OR = 1.84, 95% CI: 1.62–2.06, p < 0.001). Subgroup analysis showed this association was consistent across different demographic groups, including age, gender, BMI, and smoking status. Conclusion: NHHR is significantly linked to DR risk in diabetic patients and may be a valuable biomarker for early detection and prevention strategies in clinical settings.